Odkrivanje novih informacij v bibliografskih zbirkah podatkov - Hudomalj, Emil (Knjižnica, 2005)
Databases contain information that can usually not be revealed by standard query systems. For that purpose, the methods for knowledge discovery from databases can be applied, which enable the user to browse aggregated data, discover trends, produce online reports, explore possible new associations within the data etc. Such methods are successfully employed in various fields, such as banking, insurance and telecommunications, while they are seldom used in libraries. The article reviews the development of query systems for bibliographic databases, including some early attempts to apply modern knowledge discovery methods. Analytical databases are described in more detail, since they usually serve as the basis for knowledge discovery. Data mining approaches are presented, since they are a central step in the knowledge discovery process. The key role of librarians who can play a key part in developing systems for finding new information in existing bibliographic databases is stressed.
Keywords: podatkovne zbirke; bibliografske zbirke podatkov; analitske zbirke podatkov; podatkovna skladišča; podatkovno rudarjenje; bibliotekarstvo; library science